Inovasi Material Berkelanjutan: Optimasi Penggunaan Abu Sabut Kelapa sebagai Alternatif Filler pada Aspal Beton - Nisumanti, Sartika; Putri, Yuliantini Eka; Desromi, Ferry; Qubro, Khodijah Al; Saripudin, Saripudin; Fikri, Muhammad (Universitas Batanghari Jambi, 2025)
The use of asphalt concrete (Laston) as a pavement construction material continues to increase, especially in Indonesia. Laston, which is made as a hot mix, requires filler to bind the aggregate particles. Conventional fillers such as stone ash, lime, and cement have limited supplies and high costs, so a more economical and easily available alternative is needed. This research aims to evaluate the use of coir ash as filler in a 60/70 penetration asphalt mixture and determine the optimum asphalt content (KAO) in the mixture. The test specimens were made using 4%, 4.5%, and 5% variations of coconut fiber ash (ASK) content in 6% asphalt. This research was conducted experimentally using the Marshall Test method. The results showed that the use of coir ash as filler can affect the mechanical properties of asphalt mixture. At 4% ASK content, the VIM value reached 6.939%, and the largest or closest VFA value was obtained at 5% ASK content of 44.838%. The results obtained were greater than the Bina Marga 2010 requirements, indicating a more porous mix and potentially reduced durability. However, the use of coir ash can be a sustainable and economical solution in road construction. Testing the normal AC-WC asphalt laston layer obtained an optimum asphalt content (KAO) value of 6%, with a VIM value of 4.145%, a VMA value of 17.439%, a VFA value of 76.304%, a stability value of 1446.3 kg, and a flow value of 3.19 mm.